Map Egypt: An online database for improving food and nutrition security in Egypt - CGIAR Research Program on Policies, Institutions, and Markets (2020)
MAP Egypt is publicly available. In order to effectively allocate funds, build synergies and evaluate future proposals, users can visualize and monitor the status and progress of agricultural projects categorized by sector, location, donor or common objectives, as well as track projects' key performance indicators.